The Cost of Dreams of Utopia: Neocolonialism in Juan Rulfo's Pedro Páramo and Cormac McCarthy's All the Pretty Horses. - Lee, Susan Savage (Confluencia: Revista Hispánica de Cultura y Literatura)
A literary criticism of the books "Pedro Páramo" by Juan Rulfo and "All the Pretty Horses" by Cormac McCarthy is presented. It explores the utopian visions of landscape by the characters in both novels through seeking Mexico as their ultimate destination. It discusses how the protagonists in both novels depict the intersection of American and Mexican history. An overview of the story of both novels is also given.